Understanding the career choice of undergraduates - Doong, Shiwen (2008)
A study to find out the rationale for undergraduates’ career decisions. The importance of job attributes of undergraduates was studied and followed by comparison of undergraduates’ perceptions between SMEs and MNCs and their career choice. The existence and implications of perception gap between undergraduates and graduate employees in SMEs.